2010
DOI: 10.1002/cphc.200901006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pt Shell Thicknesses on the Atomic Structure of Ru–Pt Core–Shell Nanoparticles for Methanol Electrooxidation Applications

Abstract: In this research, core-shell electrocatalysts comprising a Ru core covered with precisely controlled 1.5-3.6 atomic layers (ALs)-thick Pt atoms are synthesized. The sample with 1.5 ALs shows a 3.2-fold improvement in CO-tolerance and 2.4-fold current enhancement at the conventional battery operation potential (I(300), at 300 mV vs Ag/AgCl) during methanol oxidation as compared with conventional all-Pt nanoparticles. The origin of the enhanced performance and the atomic structure of the core-shell nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 54 publications
(103 reference statements)
4
75
0
1
Order By: Relevance
“…This result suggests that the optimal size for Ru cores of core-shell Ru@Pt electrocatalysts for MORs is approximately 2.0 nm. The thickness of the Pt shell over Ru cores is also an important factor, in which Chen et al [92] reported that the optimum thickness of Pt shells over a 1.6 nm Ru core is 1.5 atomic layers in Ru@Pt core-shellstructured electrocatalysts for MORs, and Xie et al [108] reported that three atomic layers are the optimum thickness for Pt shells over a 3 nm Ru core. Here, the difference between the two reports is a result of the structure and size of the different Ru cores.…”
Section: Ru As Corementioning
confidence: 99%
See 2 more Smart Citations
“…This result suggests that the optimal size for Ru cores of core-shell Ru@Pt electrocatalysts for MORs is approximately 2.0 nm. The thickness of the Pt shell over Ru cores is also an important factor, in which Chen et al [92] reported that the optimum thickness of Pt shells over a 1.6 nm Ru core is 1.5 atomic layers in Ru@Pt core-shellstructured electrocatalysts for MORs, and Xie et al [108] reported that three atomic layers are the optimum thickness for Pt shells over a 3 nm Ru core. Here, the difference between the two reports is a result of the structure and size of the different Ru cores.…”
Section: Ru As Corementioning
confidence: 99%
“…Here, strain effects can be affected by metals from the upper monolayer to the several atomic layers around the interface with strain effects being strongest in Pt monolayer shells in which stability is still controversial. Optimum Pt shell thicknesses are often reported to be 2~3 atomic layers [62,92,121,297,299,409] and the strain in thinner shells shows weaker dependence on nanoparticle diameters as compared with thicker shells Fig. 36 Models of pseudo-morphic monolayers of Pt on three different substrates inducing compressive strain (Ru (0001) and Pd (111)) and expansive strain (Au (111)).…”
Section: Strain Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts for DAFC anode are also very much needed since the formation of undesired by-products of alcohol decomposition has to be minimized by effective C-C bond cleavage and, at the same time, the oxidation of CO species poisoning the reaction has to be accelerated. [26][27][28][29] Pt-Ru alloy NPs have also been found useful as catalysts for the aforementioned reaction though their activity and stability under fuel cell operating conditions appeared inferior as compared to those of Ru core-Pt shell ones. 25,26,29,31,32 Studies have shown that the superb catalytic properties of Ru core-Pt shell NPs are strongly influenced by the 3D arrangement of atoms at the interface between their core and shell components.…”
mentioning
confidence: 98%
“…18,[35][36][37] Here we probed the K absorption edge of Pt species (78.395 keV; see Figure S3a) not only because of their particular importance to the catalytic properties of Ru-Pt NPs but also for obtaining diffraction data effectively "highlighting" the Pt-based and "dimming" the Ru-based components of the NPs. [24][25][26][27][28][29][30][31] The latter was critical to determining the 3D atomic arrangement at the interfaces between these components, as described below. More details of the resonant high-energy XRD experiments are given in the Methods Section of SI.…”
mentioning
confidence: 99%